Thyroxine-induced periodic paralysis: a rare complication of nutritional supplements. Issue 1 (13th December 2018) - Cheema, Muhammad Arslan; Zain, Muhammad Abdullah; Cheema, Khadija; Ullah, Waqas
Abstract : The consumption of daily nutritional supplements has risen dramatically all over the world. Many people believe that dietary supplements, if not useful, are at least safe to fulfil small dietary gaps. Many nutritional supplements have not been approved by Federal Drug Administration due to their unregulated active ingredients, but they are available as over the counter. One of the active ingredients, exogenous triiodothyronine (T3), has been reported in dietary supplements. We present a case of sudden onset of tetraparesis. Laboratory workup showed hypokalaemia, low thyroid-stimulating hormone and thyroxine (T4) but normal T3 and thyroglobulin levels. The radioiodine uptake scan also showed reduced uptake. After aggressive serum potassium correction and stopping supplements, his condition got improved. So the suspicion of exogenous T3-induced thyrotoxic periodic paralysis was confirmed.